2007
DOI: 10.1002/anie.200604651
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication of Human Natural Killer Cells by Nanosized Phosphonate‐Capped Dendrimers

Abstract: Non‐natural born killers: The addition of phosphorus‐containing dendrimers capped with phosphonate end groups to cultures of human peripheral blood mononuclear cells (white blood cells) strongly stimulates the selective multiplication of functional natural killer (NK) cells (see picture), which play a key role in anticancer immunity. Both the generation of the dendrimer and the type of end groups are important criteria for the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 36 publications
1
104
0
Order By: Relevance
“…The TamBP phenol arises from a Kabachnik-Fields reaction, which is a three-component procedure involving aqueous formaldehyde, tyramine and dimethylphosphite. [22] The third key step of this procedure is a standard dealkylation [27] of the methyl phosphonic acid esters with bromotrimethylsilane in acetonitrile leading to a silylated tetraphosphonic acid-terminated dendrimer De. The latter, too sensitive towards hydrolysis to be isolated, is subsequently subjected to methanolysis to give a phosphonic acid-terminated dendrimer Df.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TamBP phenol arises from a Kabachnik-Fields reaction, which is a three-component procedure involving aqueous formaldehyde, tyramine and dimethylphosphite. [22] The third key step of this procedure is a standard dealkylation [27] of the methyl phosphonic acid esters with bromotrimethylsilane in acetonitrile leading to a silylated tetraphosphonic acid-terminated dendrimer De. The latter, too sensitive towards hydrolysis to be isolated, is subsequently subjected to methanolysis to give a phosphonic acid-terminated dendrimer Df.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro immunostimulating properties of this conjugate were reported to be lower than those of free hIL-3. [20] However, we have recently shown that phosphorus-containing dendrimers [21] decorated with suitable amino-bismethylene phosphonic acid derivatives on the surface were able to both promote the amplification of fully functional NK cells [22] and to provide the activation of monocytes from healthy human peripheral blood mononuclear cells (PBMC) in culture, [23] whereas the corresponding surface monomers were unable to provide such activities. Monocytes are a pivotal subpopulation of the innate immune system.…”
mentioning
confidence: 98%
“…The first generation phosphorhydrazone dendrimer functionalized by 12 azabisphosphonate groups is able to trigger the human immune system, and can induce the multiplication by several hundreds of the number of Natural Killer (NK) cells. NK cells are particularly important, as they are able to fight against various infection and numerous leukemia and carcinoma [81]. As shown by Poupot et al [82] a fluorescently labeled analogue dendrimer (Fig.…”
Section: Optical Imagingmentioning
confidence: 99%
“…[9,10] Moreover, phosphonates grafted onto the surfaces of phosphorus dendrimers display the unexpected property of dramatically and selectively promoting the multiplication of human natural killer (NK) cells, which are a key part of innate immunity. [11,12] The exceptional bioactivity behaviour of these dendrimers prompted us not only to diversify with regard to ways of attaching phosphonates onto the surfaces of known phosphorus dendrimers but also to search for new ways to synthesise phosphorus dendrimers possessing terminal phosphonate groups in order to optimize their properties and to find the best molecule for the applications discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…[12] A new alternative involves the use of "click chemistry" with dendrimers decorated with azido groups and monomers bearing acetylenic groups. [13][14][15] To test this reaction, in a first approach we treated the hexaazido core 3 with the acetylenic aminobisphosphonate 6 (Scheme 3) in the presence of CuI and diisopropylethylamine (DIPEA) as base in THF at 40°C.…”
Section: Introductionmentioning
confidence: 99%